2016
DOI: 10.1089/ten.tea.2015.0359
|View full text |Cite
|
Sign up to set email alerts
|

Cell Density and Joint microRNA-133a and microRNA-696 Inhibition Enhance Differentiation and Contractile Function of Engineered Human Skeletal Muscle Tissues

Abstract: To utilize three-dimensional (3D) engineered human skeletal muscle tissue for translational studies and in vitro studies of drug toxicity, there is a need to promote differentiation and functional behavior. In this study, we identified conditions to promote contraction of engineered human skeletal muscle bundles and examined the effects of transient inhibition of microRNAs (miRs) on myogenic differentiation and function of two-dimensional (2D) and 3D cultures of human myotubes. In 2D cultures, simultaneously i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…High expression of miR-696 in skeletal muscle suggests that it may play a role in skeletal muscle myogenesis. Previous research has shown that anti-miR-696 expression could lead to a modest increase in slow MyHC 48. However, no studies have so far been performed to determine the function of miR-696 in skeletal myoblast proliferation and its mechanism in regulating muscle cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of miR-696 in skeletal muscle suggests that it may play a role in skeletal muscle myogenesis. Previous research has shown that anti-miR-696 expression could lead to a modest increase in slow MyHC 48. However, no studies have so far been performed to determine the function of miR-696 in skeletal myoblast proliferation and its mechanism in regulating muscle cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…[102,106] Whether one of the routes may be better suited for clinical translation remains to be elucidated, although in situ transfecting scaffolds hold greater potential to exist as "off-the-shelf" products. [107] Many distinct scaffold types have been tuned to serve the purpose of miRNA delivery, including several hydrogels, [58,92,106,[108][109][110][111][112][113][114] electrospun fibers, [63,[115][116][117][118] and more prolifically porous or spongy scaffolds. [46,47,50,54,55,96,112,[119][120][121][122][123][124][125][126][127][128][129][130] Before reviewing the details of their applications, summarized in Table 2 and described further in the next section, we will discuss the key characteristics making these materials amenable to miRNA delivery.…”
Section: Scaffolds For Microrna Deliverymentioning
confidence: 99%
“…[133] In order to specifically adapt any scaffold to miRNA delivery, the material must retain the miRNA complexes while facilitating their sufficient exposure to the infiltrating cells. [134] Reciprocally, the presence of miRNA Enhanced expression of PGC-1a, and contractile force 2 weeks myotubes culture [111] Muscle complexes in the scaffold structure must not negatively affect its mechanical and structural features or deter cellular retention and attachment to the scaffold. [135] Depending on the nature of their components, biomaterials are typically classified as synthetic, natural, ceramics, or composites, that is, combinations of these.…”
Section: Scaffolds For Microrna Deliverymentioning
confidence: 99%
See 2 more Smart Citations